Evaluation of surface roughness and power consumption in machining FCD 450 using coated and uncoated irregular milling tools - Arsyad, Fitriyanti (2015)
Machining is the most important manufacturing process in these modern industries especially for producing automotive component. Quality, productivity and cost saving in manufacturing industries is one of the main manufacturer focus in making mechanical product in Sapura Industry. In this project, the effects of different cutting conditions (spindle speed, feed rate, and depth of cut, machining length and machining time) on surface roughness and power consumption on FCD450 cast iron by using CNC milling machine are studied. The experimental output indicated average decrement 27.92% for surface roughness by using coated compare uncoated tool. Average decrement 9.32% for power consumption by using coated compare uncoated tool. The suggested cutting parameter for lowest surface roughness and lowest power consumption by using coated and uncoated tools are; cutting speed (3026 rev/min), feed rate (120 mm/min), depth of cut (0.75 mm), radial depth of cut (20 mm) ,machining time (73.5second) and machining length (300 mm). From the results, the optimum cutting speed (2587.95 rev/min), feed rate (280.28 mm/min), lowest depth of cut (0.75 mm), radial depth of cut (10.88 mm), machining time (72.5 second) and machining length (269.4 mm) is suggested for further analysis and experiment of coated solid carbide cutting tools to get optimum performance. From the results experiments, it can be concluded that using coated solid carbide give optimum results in the term of surface roughness, power consumption, tool wear and tool life as compared to uncoated tools in milling. High quality surface and high productivity is obtained using coated tool compare uncoated tools because using coated is more economical in terms of energy and power requirements which meet the high demand of the industry nowadays.